Human umbilical cord mesenchymal stem cells induction in peri-implantitis Rattus norvegicus accelerates and enhances osteogenesis activity and implant osseointegration - Nike Hendrijantini; Mefina Kuntjoro; Bambang Agustono; Ratri Maya Sitalaksmi; Muhammad Dimas Aditya Ari; Marcella Theodora; Rudy Effendi; Ivan Setiawan Djuarsa; Jennifer Widjaja; Agung Sosiawan; Guang Hong (Elsevier, 2023)
Background: Peri-implantitis additional treatment generally aims to repair damaged tissue through a regenerative approach. Human umbilical cord mesenchymal stem cells (hUCMSCs) produce a high osteogenic effect and are capable of modulating the immune system by suppressing inflammatory response, modulating bone resorption, and inducing endogenous osteogenesis. Aim: This study was intended to discover the effect of hUCMSCs on an implant osseointegration process in peri-implantitis rat subjects as assessed by several markers including interleukin-10 (IL-10), transforming growth factor-β (TGF-β), receptor activator of nuclear factor kappa- β ligand (RANKL), bone morphogenic protein (BMP-2), osterix (Osx), and osteoprotegerin (OPG). Material and methods: The research design implemented during this study represented a true experimental design incorporating the use of Rattus norvegicus (Wistar strain) as subjects. Results: Data analysed by means of a Brown Forsythe test indicated differences between the increase in BMP-2 expression (p < 0.000) and Osx expression (p < 0.001) and between RANKL expression (p < 0.001, Tukey HSD) and OPG expression (p < 0.000, Games Howell). Conclusion: According to the findings of this research, hUCMSCs induction is successful in accelerating and enhancing osteogenic activity and implant osseointegration in peri-implantitis rat subjects.